LEARNING OBSTACLE SISWA SEKOLAH DASAR PADA MATERI BILANGAN DESIMAL - Riska Oktaviani Tristania Pulungan (Journal of Professional Elementary Education, 2023)
Understanding decimal numbers is very important to have. Many things in everyday life involve the concept of decimal numbers. Limitations in interpreting decimal numbers can result in errors, such as inaccuracies in measurement activities. In addition, it can also cause obstacles in learning other mathematical material, such as geometry and statistics. Given the importance of understanding decimal numbers, elementary school students need to interpret them properly. This study aims to analyze student learning obstacles related to decimal number material. Through this research, it is hoped that it can become material for reflection, especially for educators to design learning activities that can minimize the possibility of the emergence of similar learning obstacles presented in this study. This study aims to analyze learning obstacles related to decimal number material. Through this research, it is hoped that it can become material for reflection, especially for educators to design learning activities that can minimize the possibility of the emergence of similar learning obstacles presented in this study. This research was conducted on sixth grade elementary school students. Students are given questions related to decimal numbers. The results of student answers were analyzed, then students were interviewed. Interviews were conducted to find out more clearly about the learning barriers experienced by students. The results show that the difficulty in understanding decimal numbers is caused by students' learning experiences that are not meaningful to students. Students learn how to perform mathematical operations on decimal numbers, but have no conceptual knowledge about these numbers